In Situ FTIR Observation of the Polymer FM Enrichment at the EHL Contact - Reina Goto (Japanese Society of Tribologists, 2020)
Research interests recently increased in studying polymer-type friction modifiers (polymer FM) consisting of a polymer backbone and a functional group because of their good friction reduction capability. However, there is no clear verification of their working mechanisms. Therefore, the polymer FM behavior at the contact region must be understood to provide mechanistic information and design further-improved polymer FMs. For this purpose, in situ observation techniques have been applied to the chemical analysis of the oil film formed from a polymer FM using a micro-Fourier transform infrared spectrometer. The experimental results indicate that the polymer concentrations at the Hertzian contact drastically increased, exceeding the bulk concentration of oil. The following new friction reduction mechanism is proposed based on the clarified polymer FM concentration: the concentrated adsorption layer of the polymer FM prevents direct contact of the surface asperities.